2011
DOI: 10.1111/j.1600-0447.2011.01777.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive alterations in patients with non‐affective psychotic disorder and their unaffected siblings and parents

Abstract: Cognitive functioning is a candidate intermediate phenotype given significant small to large alterations in patients and intermediate alterations in first-degree relatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 55 publications
(111 reference statements)
1
36
2
Order By: Relevance
“…Unlike previous studies that reported better cognitive functioning in lifetime, but not recent, cannabis using patients (Joyal et al 2003;Potvin et al 2005;Fernandez-Serrano et al 2011;Meijer et al 2012), the association between lifetime infrequent stimulant use and better cognition in our study was small and insignificant. It has been suggested that patients who use substances need better cognitive skills to obtain drugs, which may explain the higher levels of premorbid adjustment in comparison to never using patients (Murray et al 1992).…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike previous studies that reported better cognitive functioning in lifetime, but not recent, cannabis using patients (Joyal et al 2003;Potvin et al 2005;Fernandez-Serrano et al 2011;Meijer et al 2012), the association between lifetime infrequent stimulant use and better cognition in our study was small and insignificant. It has been suggested that patients who use substances need better cognitive skills to obtain drugs, which may explain the higher levels of premorbid adjustment in comparison to never using patients (Murray et al 1992).…”
Section: Discussioncontrasting
confidence: 99%
“…As mild cognitive alterations are present in non-affected relatives, 54,55 it may be hypothesized that subclinical expression of symptoms are associated with this WM intermediate phenotype, which will be the topic of further investigation.…”
Section: Findings In Siblingsmentioning
confidence: 99%
“…2,5,8 Nevertheless, the mechanisms underlying this association are not well understood. 1,2,9 Cognitive dysfunctions are central to schizophrenia and BD, [10][11][12][13] and recent data suggest that the cognitive decline begins in childhood. 14,15 The cognitive impairments that are typically shared by patients with schizophrenia and BD 12,16,17 have a genetic basis, 18,19 which does not preclude environmental influences from further impacting the developmental trajectory.…”
Section: Introductionmentioning
confidence: 99%